Notes on the Theatrical Offer in Contemporary Romania - TĂTAR VÎSTRAŞ, Ivona (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
This paper is a note on the theatrical offer in Romania and it seeks to lay emphasis on some of the elements that are essential to the understanding of theatrical marketing in this geographic area. The focus is on the understanding and the definition of the theatrical product and on repertory construction. Furthermore, the article includes a series of economic analyses conducted in order to complete the theoretical examination, as well as case studies material to our research topic.